Aggressive perpetration and victimization among Polish male and female adolescents: the role of attachment to parents and self-control - Li, Jian-Bin (Crime & delinquency, 2019)
Aggressive perpetration and victimization are a salient problem among Polish adolescents. Based on the general theory of crime, this study explored the associations between attachment to parents and self-control with perpetration and victimization among Polish adolescents (N = 355, 146 boys and 209 girls). Results showed that (a) secure attachment to father related to less perpetration and victimization among boys and girls, whereas secure attachment to mother associated with less perpetration and victimization among girls; (b) secure attachment to father was related to better self-control for boys and girls; and (c) self-control related to reduced victimization and mediated the “attachment to father—victimization” association among girls. These findings suggest that generalizability of the general theory of crime in Polish adolescents is limited.